Infrageneric placement of the Southern Hemisphere taxa of Anemonastrum and Knowltonia earlier included in Anemone sensu lato (Ranunculaceae) - Mosyakin, S.L.; de Lange Peter J.; Bulakh, O.V. (Український ботанічний журнал, 2018)
The genera Anemonastrum and Knowltonia earlier usually included in Anemone sensu lato (Ranunculaceae: Anemoneae) were recently proposed to be recognized in expanded circumscriptions, based on molecular phylogenetic findings and partly also morphological and biogeographical evidence. Both these genera contain some representatives that are noteworthy from morphological and biogeographical viewpoints, and the general ranges of these genera (combining the ranges of their included species) demonstrate remarkable continent-scale disjunctions. In particular, Knowltonia in its new circumscription (corresponding to Anemone sect. Pulsatilloides sensu Hoot et al., 2012) contains southern African and some American taxa (mostly South American ones, including Oreithales, Barneoudia, etc.), and K. crassifolia from Tasmania. Anemonastrum (corresponding to Anemone subg. Anemonidium sensu Hoot et al., excluding Hepatica) is mainly Eurasian, but it also includes several North American species, as well as A. antucense from southern South America and A. tenuicaule from New Zealand. Species of the newly outlined Anemonastrum and Knowltonia were placed in various infrageneric taxa of Anemone sensu lato. Following the re-circumscription of genera, it is now timely to nomenclaturally update and partly re-circumscribe the relevant infrageneric taxa earlier treated in Anemone sensu lato. Here we propose the following new combinations at the section and subsection ranks: Knowltonia sect. Mexicanae (Starod.) Mosyakin & de Lange, comb. nov. (incl. K. mexicana); sect. Crassifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. crassifolia); sect. Rigidae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. Knowltonia hootae = Anemone rigida, K. hepaticifolia, K. moorei); sect. Meridium (Starod.) Mosyakin & de Lange, comb. nov. (incl. K. helleborifolia and K. peruviana), sect. Sellowiae (Hoot) Mosyakin & de Lange, comb. nov. (incl. K. sellowii and K. assisbrasiliana); sect. Oreithales (Schltdl.) Mosyakin & de Lange, comb. nov. (incl. K. integrifolia); sect. Barneoudia (Gay) Mosyakin & de Lange, comb. nov. (incl. K. balliana, K. chilensis, K. major); sect. Pulsatilloides (DC.) Mosyakin & de Lange, comb. nov.; [sect. Pulsatilloides] subsect. Alchemillifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. caffra and K. fanninii), and [sect. Pulsatilloides] subsect. Pinnatifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. tenuifolia). The new species-rank combination Knowltonia caffra (Eckl. & Zeyh.) Christenh. & Byng ex Mosyakin & de Lange, comb. nov. is validated. The new subsectional name Anemonastrum sect. Anemonidium subsect. Makariri de Lange & Mosyakin, subsect. nov. is proposed; this new subsection houses Anemonastrum antucense from South America and A. tenuicaule from New Zealand.